Social contagion of pain and fear results in opposite social behaviors in rodents: meta- analysis of experimental studies - Du, Rui; Yu, Yang; Wang, Xiao-Liang; Lu, Guofang; Chen, Jun (Frontiers in Behavioral Neuroscience, 2024)
Introduction The study aimed to explore the key factors influencing emotional valence in rodents, focusing on the critical elements that distinguish the contagion processes of fear and pain. Methods Through a systematic review and meta-analysis, we examined behavioral outcomes of rodents exposed to painful or fearful catastrophes to see whether they are prosocial or antisocial through three-chamber test and dyadic social interaction paradigm. Results Fear contagion, particularly when witnessed, leads to social avoidance behavior, unaffected by sex difference but more pronounced with age. In contrast, pain contagion promotes social approach and caring/helping behaviors. Discussion The present study demonstrates that the emotional valence induced by pain contagion is quite different from fear contagion and this difference may result in different motivations and social behaviors, namely, social contagion of pain is likely to be more associated with prosocial behaviors, however, social contagion of fear is likely to be more associated with antisocial behaviors. Systematic Review Registration PROSPERO (CRD42024566326).